PROMOTING SELF-EXPRESSION AND POSITIVE VISUALIZATION THROUGH ART EDUCATION IN NON-ART-SPECIALIZED PROSPECTIVE TEACHERS - Lakhyani, Susmita (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In today’s time where there is always a sense of competition in every individual and apparent dissatisfaction towards life, individuals are more stressed and struggling with mental health. Positive visualization and meditation in teacher education will help future educators deal with stress, self-doubt, and burnout. This paper investigates the incorporation of creative pedagogies in the education of non-art-specialized prospective teachers drawing upon a workshop–based pedagogy to express their emotions and develop a positive outlook. This research is qualitative. 40 prospective teachers participated in the workshop, organized into five phases: Introductory activity – self-reflection and expression; Re-writing activity – transforming negative thoughts; Positive visualization and meditation with probes; Creation of artwork; and Reflection. The workshop's main purpose was to promote self -expression and help participants become more optimistic and encourage them to use visualization and drawing to understand and nurture their positive emotions. Through self-expression opportunities provided in this workshop, participants were encouraged to ponder about their emotions. The activities encouraged not only creativity amongst the participants but also enabled them to uplift their own self and identify their innate potential. It helped in enhancement of personal experiences and understanding of the place of arts in education. This study envisions the creative component in the teacher education program. It demonstrates that transforming teacher trainees’ outlook and development is possible through incorporating art within the curriculum.